Kedudukan Hukum Adat: Sebuah Perbandingan Hukum Positif di Beberapa Negara - Mulyoto, Galih Puji; Mulyono, Galih Puji; Laila, Khotbatul; Budiastanti, Dhaniar Eka; Bidasari, Anindya; Wisuda, Selvia (Universitas Widya Gama Malang, 2024)
The existence of customary law in positive law often creates ambiguity in the implementation of law enforcement and legal sources. There is a problem here with this principle placing customary law as a source of law. The purpose of this paper is to provide input on the position of customary law in positive law in Indonesia by comparing several Anglo-Saxon and civil law countries. This research method uses normative legal research with a comparative approach. The results and discussion in this study describe the position of customary law in Indonesia, the Philippines, Malaysia, and Brunei Darussalam. The positive laws of these countries regulate the position of customary law in its position as a source of law and law enforcement. Customary law in the Philippines is a dispute resolution tool related to community problems with customary law so that there is no overlap in the enforcement of laws and regulations. Customary law in Malaysia is not codified in the customary law, it is codified in the law. Courts do not play a role in the development of customary law. Customary law is also developed by the courts. Positive law that applies to all society positive law applies to all society. Brunei Darussalam still lives in society and is still widely used positive law is the law that applies to all communities and customary law is the main source of law in Brunei Darussalam.